Defending the Environment: Civil Society Strategies to Enforce International Environmental Law - Malone Linda A. (America : Island Press, 2006)
Defending the Environment provides the means for nongovernmental organizations, community groups, and individuals to bring environmental and public health problems to the attention of international courts, tribunals, and commissions, or to their domestic counterparts. It suggests specific strategies and provides detailed information for taking action. This revised and updated edition also contains new case studies of the application of those strategies that has occurred in recent years.
Each chapter provides a description of the institutional mechanisms that can potentially receive, review, and remedy the alleged violation, along with a set of guidelines that explain how the reader can employ a particular strategy, and an example that indicates the effectiveness of a given strategy. In addition, the book offers an appendix that lists individuals and organizations who can assist with the various strategies described.
Defending the Environment represents the first concise, comprehensive guide to international environmental law and institutions that offers readers hands-on strategies for addressing environmental and public health problems.
Keywords: Environmental law, international